Application of Six Sigma Dmaic and Kaizen Methods In Efforts to Improve The Quality of T-Shirt Isles Banana Seven Products in Textile Industry - Dimas Febriano Adinoegoro (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2019)
Application of Six Sigma Dmaic and Kaizen Methods In Efforts to Improve The Quality of T-Shirt Isles Banana Seven Products in Textile Industry. Textile Industry Company is a company engaged in manufacturing that produces textiles and garments. The Textile Industry Company in producing isles banana seven t-shirt clothing has a problem, namely the relatively large number of defects in production. The percentage of company disability in producing isles banana seven t-shirt clothing can reach 13%. see problems in the Textile Industry Company company that has a high percentage of product defects. Researchers will conduct quality control with the six sigma and kaizen DMAIC methods to reduce the number of disabilities and control disability in companies in producing isles banana seven t-shirt products. Critical To Quality (CTQ) for the most defects in the product of banana seven t-shirt is 4, namely jumping stitches (25.15%), broken stitching (23.96%), gross (22.50%), and perforated (14) , 63%). The DPMO for the isles banana seven t-shirt is 24336 units with a sigma capability of 3.47-sigma. The results of the analysis in kaizen prioritize the need for periodic checks of all facilities used.